Politics and religion in the United States - Corbett, Michael 1943- (Garland reference library of social science, 1999)
A thorough discussion of historical origins of religion in political life, constitutional matters, public opinion, and the most relevant groups, all while taking theology seriously. Revisions include fully updating all the public opinion data, fuller incorporation of voting behavior among different religious and demographic groups, enhanced discussion of minority religions such as Mormonism and Islam, and new examples throughout.